Evaluation of the Self-Help Housing Stimulus Program (BSPS) in Serang City - Rika Yulia Putri (Ambidextrous Journal of Innovation Efficiency and Technology in Organization, 2026)
The Self-Help Housing Stimulant Assistance Program (BSPS) is a government policy to improve the quality of housing for low-income communities. However, its implementation in Serang City still faces various obstacles, such as budget limitations, administration, fund disbursement, and community participation. This study aims to evaluate the implementation of the BSPS Program in Serang City using the CIPP evaluation model, which includes context, input, process, and product. The study used a qualitative approach with descriptive methods. Research informants were determined through a purposive sampling technique involving elements of the Housing and Settlement Areas Agency, the Banten Provincial Housing Provision Center, Bank Jabar Banten, field facilitators, and community beneficiaries. Data were collected through observation, in-depth interviews, and documentation, then analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. Data validity was tested through source triangulation, technical triangulation, and member checking. The results showed that the program's goals, objectives, and benefits had been achieved well, marked by improved housing quality, recipient welfare, and coordination between stakeholders. The main obstacles remain limited budget, administration, public understanding, and participation in mutual cooperation. The study concluded that the BSPS Program in Serang City has been quite effective, but still requires strengthening outreach, validating recipient data, simplifying administration, improving coordination, and adjusting the amount of assistance to ensure optimal and sustainable program implementation